2011
DOI: 10.1016/j.ultsonch.2010.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-promoted synthesis of 3-trichloromethyl-5-alkyl(aryl)-1,2,4-oxadiazoles

Abstract: The alternative synthesis of 12 1,2,4-oxadiazoles using ultrasound irradiation from trichloroacetoamidoxime and acyl chlorides is reported. Seven of them are novel compounds. The 3-trichloromethyl-5alkyl(aryl)-1,2,4-oxadiazoles have been synthesised in better yields and shorter reaction times compared to the conventional method. This protocol can be applicable for preparation of 1,2,4-oxadiazoles containing aryl or alkyl groups attached at their C-5 side-chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…43 It is also possible to find protocols employing ultrasound irradiation to synthesize 1,2,4-oxadiazoles (29), as reported by Bretanha et al 44 Short reaction times (15 min) and high yields (84-98%) were reported for the reaction between trichloroacetoamidoxime (27) and the properly substituted benzoyl chlorides (28) in ethyl acetate as solvent (Scheme 4). 44 In a different approach, Yoshimura et al 45 reacted nitrile oxides (34) and nitriles (31) to obtain 1,2,4-oxadiazoles (32). Hydroxy(aryl)iodonium (IBA-OTf, 33) was employed allowing the formation in situ of nitrile oxides (34) from the respective nitriles (31).…”
Section: Differences Between 124-and 134-oxadiazolesmentioning
confidence: 89%
“…43 It is also possible to find protocols employing ultrasound irradiation to synthesize 1,2,4-oxadiazoles (29), as reported by Bretanha et al 44 Short reaction times (15 min) and high yields (84-98%) were reported for the reaction between trichloroacetoamidoxime (27) and the properly substituted benzoyl chlorides (28) in ethyl acetate as solvent (Scheme 4). 44 In a different approach, Yoshimura et al 45 reacted nitrile oxides (34) and nitriles (31) to obtain 1,2,4-oxadiazoles (32). Hydroxy(aryl)iodonium (IBA-OTf, 33) was employed allowing the formation in situ of nitrile oxides (34) from the respective nitriles (31).…”
Section: Differences Between 124-and 134-oxadiazolesmentioning
confidence: 89%
“…Chemical reactions can be catalyzed under ultrasound irradiation through acoustic cavitation: formation, growth and collapse of bubbles [48]. Cavitation process transforms the ultrasonic energy into hot spots which can be considered as microreactors [49]. In other words, cavitation provides intense local temperature, high pressures and cooling rates [50].…”
Section: Synthesis Of 2-aryl Substituted Benzoxazolesmentioning
confidence: 99%
“…Mechanistically the process passes by the formation of an intermediate 4,5-dihydro-1,2,4-oxadiazole (oxadiazoline) that undergoes the oxidation in the reaction conditions. Scheme 12 -Reaction scheme for the synthesis of 1,2,4-oxadiazole proposed by ADIB et al (2006) Recently it was published in the literature a synthetic procedure using irradiation by ultrasound (USI) in the synthesis of oxadiazole (BRETANHA et al, 2011). In this work the authors report the synthesis of 12 oxadiazole derivatives containing the trichloromethyl group in the position 3 and different alkyl and aryl groups in the position 5 obtained by the reaction of trichloroacetamidoxime with the appropriated acyl chloride (Scheme 13).…”
Section: Scheme 9 -Reaction Conditions Used By Kaboudin and Saadati (mentioning
confidence: 99%